Genome-Wide Identification of Triticum aestivum Xylanase Inhibitor Gene Family and Inhibitory Effects of XI-2 Subfamily Proteins on Fusarium graminearum GH11 Xylanase - Liu, Yang; Han, Nannan; Wang, Sheng; Chen, Can; Lu, Jie; Riaz, Muhammad Waheed; Si, Hongqi; Sun, Genlou; Ma, Chuanxi (Frontiers in Plant Science, 2021)
Triticum aestivum xylanase inhibitor (TaXI) gene plays an important role in plant defense. Recently, TaXI–III inhibitor has been shown to play a dual role in wheat resistance to Fusarium graminearum infection. Thus, identifying the members of the TaXI gene family and clarifying its role in wheat resistance to stresses are essential for wheat resistance breeding. However, to date, no comprehensive research on TaXIs in wheat (Triticum aestivum L.) has been conducted. In this study, a total of 277 TaXI genes, including six genes that we cloned, were identified from the recently released wheat genome database (IWGSC RefSeq v1.1), which were unevenly located on 21 chromosomes of wheat. Phylogenetic analysis divided these genes into six subfamilies, all the six genes we cloned belonged to XI-2 subfamily. The exon/intron structure of most TaXI genes and the conserved motifs of proteins in the same subfamily are similar. The TaXI gene family contains 92 homologous gene pairs or clusters, 63 and 193 genes were identified as tandem replication and segmentally duplicated genes, respectively. Analysis of the cis-acting elements in the promoter of TaXI genes showed that they are involved in wheat growth, hormone-mediated signal transduction, and response to biotic and abiotic stresses. RNA-seq data analysis revealed that TaXI genes exhibited expression preference or specificity in different organs and developmental stages, as well as in diverse stress responses, which can be regulated or induced by a variety of plant hormones and stresses. In addition, the qRT-PCR data and heterologous expression analysis of six TaXI genes revealed that the genes of XI-2 subfamily have double inhibitory effect on GH11 xylanase of F. graminearum, suggesting their potential important roles in wheat resistance to F. graminearum infection. The outcomes of this study not only enhance our understanding of the TaXI gene family in wheat, but also help us to screen more candidate genes for further exploring resistance mechanism in wheat.